Death and the afterlife in Byzantium: the fate of the soul in theology, liturgy, and art - Marinis, Vasileios (Cambridge University Press, 2017)
For all their reputed and professed preoccupation with the afterlife, the Byzantines had no systematic conception of the fate of the soul between death and the Last Judgement. Death and the Afterlife in Byzantium marries for the first time liturgical, theological, literary, and material evidence to investigate a fundamental question: what did the Byzantines believe happened after death? This interdisciplinary study provides an in-depth analysis and synthesis of hagiography, theological treatises, apocryphal texts and liturgical services, as well as images of the fate of the soul in manuscript and monumental decoration. It also places the imagery of the afterlife, both literary and artistic, within the context of Byzantine culture, spirituality, and soteriology. The book intends to be the definitive study on concepts of the afterlife in Byzantium, and its interdisciplinary structure will appeal to students and specialists from a variety of areas in medieval studies.